Confined transverse electric phonon polaritons in hexagonal boron nitrides - Musa, Muhyiddeen Yahya (2019)
We predict the existence of confined transverse electric (TE) phonon polaritons in an ultrathin hexagonal boron nitride (hBN) slab below hBN's second transverse optical frequency. The skin depth of TE phonon polaritons can be decreased to subwavelength scale by increasing the thickness of hBN to several nanometers. Due to the strong spatial confinement, these TE phonon polaritons, different from TE graphene plasmons, can stably exist even when the permittivities of the superstrate and substrate are largely different. These revealed advantages of TE phonon polaritons might lead to potential applications of hBN in the manipulation of TE waves, such as the design of novel waveguides, polarizers, and the exploration of negative refraction between TE polaritons.